ETIKA JURNALISTIK PERSPEKTIF AL-QUR’AN - Sauda’, Limmatus (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Today, journalistic world increasingly find its freedom. Its effects can nolonger be taken lightly. Therefore, there should be some rules to control and tocommand the journalists, not to restrict it. Related to this issue, the normativesources of Islam, the Qur'an encourage people to speak the truth, honestly and inaccordance with the facts (QS. al-Ahzab [33]: 70). In another verse, Allah alsoorders to stay away from the prejudice that would bring doubt and untruth (QS. al-Hujurat [49]: 12), nor slander broadcast news in various forms (QS. al-Nur [24]:19) and the reader should check the truth first before receive it (QS. al-Hujurat[49]: 6). Some of these verses are references to the news makers or journalist intheir work, as well as for the consumers when they receive the news.At this paper, the dialogue between the Qur'an with the phenomenon ofjournalism displayed by using the comparative nature of the interconnectionpattern (in this case the journalistic ethics of the Press Council and the decision ofthe Indonesian Broadcasting Commission and journalistic ethics in the Qur'an).About exegesis of the Qur'an, the method is used is ijmali and it did not interpretall of the content of verse, only partly related to the news.